Jails, prisons, and the health of urban populations: A review of the impact of the correctional system on community health - Freudenberg, Nicholas (Springer-Verlag, 2001)
This review examined the interactions between the correctional system and the health of urban populations. Cities have more poor people, more people of color, and higher crime rates than suburban and rural areas; thus, urban populations are overrepresented in the nation's jails and prisons. As a result, US incarceration policies and programs have a disproportionate impact on urban communities, especially black and Latino ones. Health conditions that are overrepresented in incarcerated populations include substance abuse, human immunodeficiency virus (HIV) and other infectius diseases, perpetration and victimization by violence, mental illness, chronic disease, and reproductive health problems. Correctional systems have direct and indirect effects on health. Indirectly, they influence family structure, economic opportunities, political participation, and normative community values on sex, drugs, and violence. Current correctional policies also divert resources from other social needs. Correctional systems can have a direct effect on the health of urban populations by offering health care and health promotion in jails and prisons, by linking inmates to community services after release, and by assisting in the process of community reintegration. Specific recommendations for action and reseach to reduce the adverse health and social consequences of current incarceration policies are offered.